Cell surfactomes of two endometrial epithelial cell lines that differ in their adhesiveness to embryonic cells. Issue 4 (5th February 2014) - Bhagwat, Sonali R.; Redij, Tejashree; Phalnikar, Kruttika; Nayak, Sumeet; Iyer, Swati; Gadkar, Sushama; Chaudhari, Uddhav; Kholkute, Sanjeeva D.; Sachdeva, Geetanjali
SUMMARY Adhesiveness of the endometrial epithelium to an embryo plays a critical role in the initiation of pregnancy. Loss or gain of adhesiveness also dictates the potential of endometrial epithelial cells to metastasize, an event that can result from certain genetic insults. A proteomics‐based exploration of the "adhesiveness" these epithelial cells was employed that could identify targets that could disrupt embryo–endometrium interactions and/or metastasis of endometrial cancer cells. The present study defined the surfactomes of two human endometrial epithelial cell lines known for their differential adhesiveness to embryonic cells. Comparative, two‐dimensional electrophoretic analysis of the surfactomes of RL95‐2 (exhibiting higher adhesiveness to the embryonic cell line JAr) and HEC‐1A (exhibiting reduced adhesiveness to JAr cells) revealed 55 differentially enriched proteins. Of these, 10 proteins were identified by MALDI‐TOF/TOF or LC–MS/MS. TUBB2C, ADAMTS3, and elongation factor beta were more abundant on the HEC‐1A cell surface whereas HSP27, HSPA9, GP96, CRT, Tapasin‐ERP57, PDI, and β‐actin were more abundant on the RL95‐2 cell surface. Nano LC–MS/MS was also employed to generate a more comprehensive surfactomes of RL95‐2 and HEC‐1A. The study also demonstrated a pro‐adhesive role of CRT and HSPA9 and an anti‐adhesive role of TUBB2C populations found on the cell surface. In brief, this study identifies the cell‐surface protein complements of two human endometrial epithelial cell lines, and reveals the role of three proteins in heterotypic cell adhesion. Mol. Reprod. Dev. 81: 326–340, 2014. © 2014 Wiley Periodicals, Inc.